Phenotypic and molecular characterisation of type 3 von Willebrand disease in a cohort of Indian patients - Ahmad, Firdos; Budde, Ulrich; Jan, Rifat; Oyen, Florian; Kannan, Meganathan; Saxena, Renu; Schneppenheim, Reinhard (Thrombosis and Haemostasis, 2013)
Severe type 3 VWD (VWD3) is characterised by complete absence or presence of trace amounts of non-functional von Willebrand factor (VWF). The study was designed to evaluate the VWF mutations in VWD3 patients and characterise the breakpoints of two identified homozygous novel large deletions. Patients were diagnosed by conventional tests and VWF multimer analysis. Mutation screening was performed in 19 VWD3 patients by direct sequencing of VWF including flanking intronic sequence and multiplex ligation-dependent probe amplification (MLPA) analysis. Breakpoint characterisation of two identified novel large deletions was done using walking primers and long spanning PCR. A total of 21 different mutations including 15 (71.4%) novel ones were identified in 17 (89.5%) patients. Of these mutations, five (23.8%) were nonsense (p.R1659*, p.R1779*, p.R1853*, p.Q2470*, p.Q2520*), one was a putative splice site (p.M814I) and seven (33.3%) were deletions (p.L254fs*48, p.C849fs*60, p.L1871fs*6, p.E2720fs*24) including three novel large deletions of exon 14–15, 80,830bp (−41510_657+7928A*del) and 2,231bp [1534–2072T_c.1692G*del(p.512fs*terminus)] respectively. A patient carried gene conversion comprising of pseudogene harbouring mutations. The missense mutations (p.G19R, p.K355R, p.D437Y, p.C633R, p.M771V, p.G2044D, p.C2491R) appear to play a major role and were identified in seven (36.8%) patients. In conclusion, a high frequency of novel mutations suggests the high propensity of VWF for new mutations. Missense and deletion mutations found to be a common cause of VWD3 in cohort of Indian VWD3 patients. Breakpoints characterisation of two large deletions reveals the double strand break and non-homologous recombination as deletions mechanism.
Keywords: Type 3 VWD; Phenotype and genotype; VWF mutation; Large deletion; Non-homologous recombination